1998
DOI: 10.1148/radiology.207.2.9577496
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of breast carcinomas not detected in a screening program.

Abstract: A substantial proportion of cancers that were missed in a screening program, despite double reading, were found with this detection method at less than one false-positive finding per image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…The diagnostic process of radiologists can be improved by the use of computers [7][8][9][10][11]. Pattern-recognition techniques have been designed to draw the attention of the radiologist to regions in mammograms that need careful scrutiny and interpretation [12]. Fully automated methods can screen chest radiographs for features of tuberculosis [13].…”
mentioning
confidence: 99%
“…The diagnostic process of radiologists can be improved by the use of computers [7][8][9][10][11]. Pattern-recognition techniques have been designed to draw the attention of the radiologist to regions in mammograms that need careful scrutiny and interpretation [12]. Fully automated methods can screen chest radiographs for features of tuberculosis [13].…”
mentioning
confidence: 99%
“…This means the sensitivity of mammography for detecting breast cancer can be significantly reduced in the case of dense breasts [5]. Retrospective studies have shown that in current breast cancer screening 10% to 25% of tumors are missed by radiologists [6,7] and some of these false negative results can be explained by higher breast density.…”
Section: Introductionmentioning
confidence: 99%
“…Currently much effort is directed towards the development of Full-Field Digital Mammography (FFDM) and soft-copy reading. Soft-copy reading in combination with digital and digitized mammograms offers opportunities for the integration of Computer-Aided Detection (CAD) 4,5,6 , immediate access to image enhancement 7 , efficient and flexible organization of double reading, tele-mammography and tele-consultation on a regional and international level, and electronic image archiving and retrieval (PACS). In addition, soft-copy reading presents promising new opportunities to increase both the sensitivity and specificity of screening radiologists with CAD, computer-aided interpretation 8,9,10,11 , computer-assisted training, and automated reader in-service monitoring.…”
Section: Introductionmentioning
confidence: 99%